2019
DOI: 10.3390/microorganisms7050113
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacteria Persistence in a Cell Model Mimicking Alveolar Macrophages

Abstract: Nontuberculous Mycobacteria (NTM) respiratory infections have been gradually increasing. Here, THP-1 cells were used as a model to evaluate intracellular persistence of three NTM species (reference and clinical strains) in human alveolar macrophages. The contribution of phagosome acidification, nitric oxide (NO) production and cell dead on NTM intracellular fate was assessed. In addition, strains were characterized regarding their repertoire of virulence factors by whole-genome sequencing. NTM experienced diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 85 publications
(123 reference statements)
0
18
0
Order By: Relevance
“…They also found that, overall, M. smegmatis and M. fortuitum were better biofilm formers than M. chelonae (Sousa et al, 2015). In a subsequent study from the same group, infection with M. smegmatis, M. fortuitum (clinical and reference strains), and M. avium (clinical and reference strains) were compared in THP-1 cells (Sousa et al, 2019). They found that M. smegmatis and reference strain of M. fortuitum were cleared relatively quickly in the macrophages whereas both strains of M. avium and the clinical strain of M. fortuitum were able to replicate.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…They also found that, overall, M. smegmatis and M. fortuitum were better biofilm formers than M. chelonae (Sousa et al, 2015). In a subsequent study from the same group, infection with M. smegmatis, M. fortuitum (clinical and reference strains), and M. avium (clinical and reference strains) were compared in THP-1 cells (Sousa et al, 2019). They found that M. smegmatis and reference strain of M. fortuitum were cleared relatively quickly in the macrophages whereas both strains of M. avium and the clinical strain of M. fortuitum were able to replicate.…”
Section: Discussionmentioning
confidence: 94%
“…Although phagosome and lysosome markers were quantified in the cells, co-localization of mycobacteria with lysosomes was not. Caspase 8 and caspase 3/7 positive cells were quantified, showing that these caspases were induced more by M. fortuitum and M. avium up to 6 h; however, after 1 day, M. smegmatis and M. fortuitum induced greater caspase 3/7 positive cells (Sousa et al, 2019). But quantitation of actual apoptotic cells (e.g., TUNEL staining) was not performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inside the host, mycobacteria are found within different cell types, but tropism to macrophages where mycobacteria are internalized into phagosomes and replicate has been highlighted by the vast majority of studies [ 10 ]. The arrest of the maturation of early mycobacterium-containing phagosomes and resistance to acidic and oxidative damage are well-known protective mechanisms of these pathogens [ 10 ].…”
Section: Introduction: Mycobacteria and The Hostmentioning
confidence: 99%